Creating athlete activists: Using sport as a vehicle to combat racism - Intosh, Andrew Mac; Martin, Eric M. (Journal of sport psychology in action, 2018)
The purpose of this article is to share information about a program designed to leverage sport as a context to discuss difficult topics including racism, prejudice, diversity, and inclusivity with student-athletes. The format of the Ross Initiative in Sports for Equality (RISE) High School Leadership Program centers on experiential learning and self-discovery with an emphasis on translation of constructs to real-world examples (Kolb, 1984; Yelon, 1996). The design of the program integrates classic social psychology principles (Allport, 1954) with more contemporary positive youth development principles (Larson, 2006). In addition to program goals, one module is overviewed to provide a snapshot of curriculum.